Privacy and legal issues in cloud computing - Cheung, Anne S. Y.; Weber, Rolf H., 1951- (Elgar law, technology and society, 2015)
Using a multi-disciplinary and comparative approach, this study examines emerging and innovative attempts to tackle privacy and legal issues in cloud computing such as personal data privacy, security and intellectual property protection. An international team of legal scholars, computer science researchers, regulators and practitioners present original and critical responses to the growing challenges posed by cloud computing. They analyse the specific legal implications pertaining to jurisdiction, biomedical practice and information ownership, as well as issues of regulatory control, competition and cross-border regulation. Law academics, practitioners and regulators will find this book to be a valuable, practical and accessible resource, as will computer science scholars interested in cloud computing issues.